Outbreak of Severe Histoplasmosis Among Tunnel Workers—Dominican Republic, 2015. (2nd December 2017) - Armstrong, Paige A; Beard, John D; Bonilla, Luis; Arboleda, Nelson; Lindsley, Mark D; Chae, Sae-Rom; Castillo, Delia; Nuñez, Ramona; Chiller, Tom; de Perio, Marie A; Pimentel, Raquel; Vallabhaneni, Snigdha
Abstract : This field investigation of the first reported outbreak of histoplasmosis in the Dominican Republic, among tunnel workers, highlights the importance of clinician awareness, appropriate treatment, and proper occupational and environmental precautions. Abstract: Background: Histoplasmosis is a fungal infection associated with exposure to bat guano. An outbreak of an unknown severe febrile illness occurred among tunnel workers in the Dominican Republic, and resulted in several deaths. We conducted an investigation to confirm etiology and recommend control measures. Methods: A case was defined as fever and ≥2 symptoms consistent with histoplasmosis in a tunnel worker, July–September 2015. We interviewed workers and family members, reviewed medical records, tested serum and urine for Histoplasma antigen/antibody, and conducted a cohort study to identify risk factors for histoplasmosis and severe infection (intensive care). Results: A crew of 36 male workers removed large amounts of bat guano from tunnels without respiratory protection for a median of 24 days per worker (range, 1–25 days). Median age was 32 years (range, 18–62 years); none were immunocompromised. Thirty (83%) workers had illness that met the case definition, of whom 28 (93%) were hospitalized, 9 (30%) required intensive care, 6 (20%) required intubation, and 3 (10%) died. The median time from symptom onset to antifungal treatment was 6 days (range, 1–11 days). Twenty-two of 34 (65%) workers had laboratory evidence of infection. Conclusions: Severe illnesses and death likely resulted from exposure to large inocula of Histoplasma capsulatum spores in an enclosed space, lack of respiratory protection, and delay in recognition and treatment. Clinician education about histoplasmosis, improved laboratory capacity to diagnose fungal infections, and occupational health guidance to protect workers against endemic fungi are recommended in the Dominican Republic.